Actividades lúdicas y su aporte al desarrollo de habilidades metalingüísticas en los estudiantes de básica superior de la Unidad Educativa León de Febres Cordero de la Parroquia San Juan período 2024- 2025 - Bonifaz Herrera, Leticia Vanessa (2025)
Play activities are essential for the development of metalinguistic skills, since they facilitate students' reflection on the use and organization of language in a creative and dynamic way. The main purpose of this project is to determine the contribution of play activities in the development of metalinguistic skills in upper elementary students of the Leon Febres Cordero Educational Unit of the San Juan parish, period 2024-2025. The study adopts a mixed method, using a descriptive, field and documentary methodology, and a non-experimental design. The population is made up of eighth, ninth and tenth grade students of EGB, together with the tutor teachers responsible for these courses. A representative sample of 96 students from parallel “A” of these grades will be chosen, and three teachers will be interviewed, one for each level, with the aim of obtaining a comprehensive perspective on the influence of recreational activities on the progress of metalinguistic skills. Through surveys and interviews, we seek to examine how these activities impact on students' ability to meditate on language, enhancing their understanding and use of language in different communicative contexts. To conclude, it is understood that ludic activities contribute significantly to the development of students' metalinguistic abilities, promoting their learning process and fostering a deeper understanding of language in different contexts.